‘Where there are many cattle’ in the Eocene of Ukraine: Review of Ambositra Masner (Hymenoptera, Diapriidae, Ambositrinae) from Rovno amber, with the description of three new species - Chemyreva, Vasilisa G.; Vasilenko, Dmitry V.; Perkovsky, Evgeny E. (Zootaxa, 2024)
Three species of the genus Ambositra: A. epicnemia sp. nov., A. bicarinata sp. nov. and A. masneri sp. nov. are described from Eocene Rovno amber. The new combination Ambositra villumi (Brazidec & Vilhelmsen) comb. nov. is suggested for the extinct diapriid wasp Basalys villumi described from Baltic amber. The female of A. villumi is described. A detailed illustration of the single extant species Ambositra famosa Masner and the original illustrated key for all known Ambositra species is given. The diagnosis of the genus Ambositra is clarified.